A kind of translucent perovskite solar cell and its preparation method and application
Patent Information
- Application Number
- CN202611131040.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-07-29
AI Technical Summary
Existing semi-transparent perovskite solar cells lack spectral modulation for high-value crops in agricultural applications. The modulation methods are limited, the spectral matching accuracy is low, and it is difficult to simultaneously optimize crop growth and improve photovoltaic power generation efficiency.
By employing ternary synergistic spectral modulation technology, a semi-transparent perovskite solar cell structure is designed through perovskite bandgap modulation, absorption layer thickness modulation, and Ag metal layer optical enhancement, thereby achieving selective utilization of the solar spectrum.
Maintaining high transmittance in the red and blue light bands, enhancing the absorption and utilization of the yellow and green light bands, improving crop photosynthetic efficiency, and optimizing photovoltaic power generation performance, thereby achieving synergistic optimization of spectral regulation and power generation.
Smart Images

Figure CN122662397B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of perovskite solar cell technology, specifically to a semi-transparent perovskite solar cell, its preparation method, and its application. Background Technology
[0002] The growth of high-value crops such as bird's nest fruit, coffee, and precious Chinese medicinal herbs is highly sensitive to spectral distribution and light intensity changes. They require photosynthetically active radiation such as red light (600-700 nm) and blue light (400-500 nm), but are also susceptible to strong light or unsuitable light spectra. Meanwhile, traditional planting methods rely on artificial lighting to maintain crop yields, resulting in high energy consumption. Furthermore, facility agriculture commonly suffers from land competition between agriculture and solar power, insufficient light energy utilization efficiency, and significant carbon emissions. Therefore, there is an urgent need to achieve synergistic optimization of light energy utilization and crop growth.
[0003] Existing crystalline silicon photovoltaic modules, lacking light transmittance and spectral modulation capabilities, significantly shade crops in agricultural applications, failing to meet their growth requirements. Semi-transparent perovskite solar cells, with their tunable bandgap and certain light transmittance, are considered a potential technology for agro-photovoltaic complementary systems and have already seen some application in building-integrated photovoltaics (BIPV). However, current technologies for color or spectral modulation of semi-transparent perovskite cells primarily focus on appearance and light transmittance, lacking functional designs tailored to the spectral needs of agriculture. They also fail to fully consider the differences in light utilization by high-value crops across different wavelengths, such as their lower efficiency in utilizing yellow-green light (500-600 nm).
[0004] Furthermore, existing semi-transparent perovskite solar cells still have significant shortcomings in spectral modulation: on the one hand, their modulation methods are relatively simple, mostly relying on single-variable adjustments of perovskite material composition or absorption layer thickness, without forming a multi-parameter synergistic modulation system; on the other hand, their spectral modulation precision is limited, with unclear transmission and absorption peak shapes, making it difficult to achieve fine screening of key bands; at the same time, existing structures lack interface modulation designs that combine metal optical enhancement structures, failing to achieve synergy between spectral modulation and electrical performance optimization.
[0005] Therefore, existing technologies cannot simultaneously optimize crop growth and improve photovoltaic power generation efficiency. It is necessary to propose a new semi-transparent perovskite cell structure that can selectively utilize the solar spectrum through multi-parameter synergistic regulation. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a semi-transparent perovskite solar cell, its preparation method, and its application. The semi-transparent perovskite solar cell of this invention maintains a high transmittance level in the 600-700 nm red light band and retains a certain transmittance level in the 400-500 nm blue light band, while simultaneously enhancing the absorption and utilization of the 500-600 nm yellow-green light band, thus better matching the light utilization characteristics of crops.
[0007] To achieve the above objectives, the technical solution designed by the present invention is as follows: This invention provides a semi-transparent perovskite solar cell, which includes an ITO conductive glass bottom electrode and a NiO electrode arranged sequentially from bottom to top. x Interface decoration layer, 4PADCB hole transport layer, FA a Cs 1- a PbI 3-b Br b Perovskite absorber layer, PCBM-C 60 Electron transport composite layer, Ag metal layer and ITO transparent top electrode; The FA a Cs 1-a PbI 3-b Br b In the perovskite absorber layer, 0 < a < 1, 0 ≤ b ≤ 3.0; The PCBM-C 60 The electron transport composite layer includes a PCBM layer and a C layer disposed on the surface of the PCBM layer. 60 layer.
[0008] Furthermore, the NiO x The thickness of the interface modification layer is 10~20 nm; the thickness of the 4PADCB hole transport layer is 10~15 nm; the FA a Cs 1-a PbI 3-b Br b The thickness of the perovskite absorber layer is 200~800 nm; the thickness of the PCBM layer is 15~20 nm; the C 60 The thickness of the layer is 20~25 nm; the thickness of the Ag metal layer is 1~10 nm; and the thickness of the ITO transparent top electrode is 200~250 nm.
[0009] Furthermore, the FA a Cs 1-a PbI 3-b Br b In the perovskite absorber layer, a is 0.95, and 0.8 ≤ b ≤ 3.0.
[0010] Furthermore, the NiO x The thickness of the interface modification layer is 10 nm; the thickness of the 4PADCB hole transport layer is 10 nm. The FA a Cs 1-a PbI 3-b Br b The thickness of the perovskite absorber layer is 300 nm, where a is 0.95 and b is 3. The thickness of the PCBM layer is 15 nm; the C 60 The thickness of the layer is 20 nm; the thickness of the Ag metal layer is 8 nm; and the thickness of the ITO transparent top electrode is 200 nm.
[0011] The present invention also provides a method for preparing the aforementioned semi-transparent perovskite solar cell, comprising the following steps: (1) The ITO conductive glass was ultrasonically cleaned, dried with nitrogen, and then treated with ultraviolet ozone to obtain the ITO conductive glass bottom electrode. (2) NiO solution was spin-coated onto the surface of an ITO conductive glass bottom electrode using a spin-coating method. After spin-coating, annealing was performed to obtain NiO. x Interface decoration layer; (3) The 4PADCB solution was spin-coated onto NiO. x The interface modification layer surface is spin-coated, and then annealed to obtain a 4PADCB hole transport layer. (4) Cesium bromide, formamidine hydrobromide, lead iodide and lead bromide are dissolved in a DMF-DMSO mixed solvent to obtain a precursor solution; (5) The precursor solution was spin-coated onto the surface of the 4PADCB hole transport layer using a spin-coating method. Chlorobenzene antisolvent was added dropwise during spin-coating. After spin-coating, annealing was performed to obtain FA. a Cs 1-a PbI 3-b Br b Perovskite absorber layer; (6) The PCBM solution was spin-coated onto the FA. a Cs 1-a PbI 3-b Br b The perovskite absorber layer is spin-coated to obtain the PCBM layer; (7) C is deposited on the surface of the PCBM layer using thermal evaporation deposition method. 60 Layer, PCBM layer and C 60 The layer combination is PCBM-C 60 Electron transport composite layer; (8) Using thermal evaporation deposition method on PCBM-C 60An Ag layer is deposited on the surface of the electron transport composite layer to obtain an Ag metal layer; (9) An ITO layer was deposited on the surface of the Ag metal layer by magnetron sputtering to obtain an ITO transparent top electrode, thus completing the fabrication of a semi-transparent perovskite solar cell.
[0012] Furthermore, in step (1), ultrasonic cleaning is performed sequentially using glass water, deionized water and anhydrous ethanol, and the ultraviolet ozone treatment time is 20~30 min; In steps (2) and (3), the concentration of the NiO solution is 10-15 mg / mL, the concentration of the 4PADCB solution is 0.5-1 mg / mL, the spin coating speed is 3000-4000 rpm, the spin coating time is 30-40 s, the annealing temperature is 100-120℃, and the annealing time is 10-15 min; the NiO x The thickness of the interface modification layer is 10~20 nm; the thickness of the 4PADCB hole transport layer is 10~15 nm. In step (4), the molar ratio of cesium bromide, formamidine hydrobromide, lead iodide and lead bromide is 0.05:0.95:0~1:0~1, the volume ratio of DMF to DMSO in the DMF-DMSO mixed solvent is 3~4:1, and the total molar concentration of the precursor solution is 0.5~1.5 mol / L. In step (5), the spin coating speed is 2000~4000 rpm, the spin coating time is 23~50 s, and chlorobenzene antisolvent is added dropwise during the 12th~42nd s of the spin coating process. The volume ratio of chlorobenzene antisolvent to precursor solution is 1:0.2~0.4. The annealing temperature is 100~120℃, and the annealing time is 20~25 min. a Cs 1-a PbI 3-b Br b The thickness of the perovskite absorber layer is 200~800 nm.
[0013] Furthermore, in step (1), ultrasonic cleaning is performed sequentially using glass water, deionized water and anhydrous ethanol, and the ultraviolet ozone treatment time is 25 min. In steps (2) and (3), the concentration of the NiO solution is 10 mg / mL, and the concentration of the 4PADCB solution is 0.5 mg / mL; the NiO x The thickness of the interface modification layer is 10 nm; the thickness of the 4PADCB hole transport layer is 10 nm. In step (4), the molar ratio of cesium bromide, formamidine hydrobromide, lead iodide and lead bromide is 0.05:0.95:0:1, the volume ratio of DMF to DMSO in the DMF-DMSO mixed solvent is 4:1, and the total molar concentration of the precursor solution is 0.7 mol / L. In step (5), the spin coating speed is 4000 rpm, the spin coating time is 23 s, and chlorobenzene antisolvent is added dropwise at the 12th second of the spin coating process. The volume ratio of chlorobenzene antisolvent to precursor solution is 1:0.27. The annealing temperature is 100℃, and the annealing time is 20 min. a Cs 1-a PbI 3-b Br b The thickness of the perovskite absorber layer is 300 nm.
[0014] Furthermore, in step (6), the concentration of the PCBM solution is 10~15 mg / mL, the spin coating speed is 7000~8000 rpm, the spin coating time is 30~35 s, and the thickness of the PCBM layer is 15~20 nm. In step (7), the evaporation rate of the thermal evaporation deposition is 0.1~0.2 Å / s; the C 60 The thickness of the layer is 20~25nm; In step (8), the evaporation rate of the thermal evaporation deposition is 0.1~0.2 Å / s; the thickness of the Ag metal layer is 1~10 nm; In step (9), the atmosphere of the magnetron sputtering method is argon, the flow rate of argon is 30~40 sccm, the power of magnetron sputtering is 45~50 W, the vacuum degree of magnetron sputtering is 0.2~0.4 Pa, and the thickness of the ITO transparent top electrode is 200~250 nm.
[0015] Furthermore, in step (6), the concentration of the PCBM solution is 10 mg / mL, the spin coating speed is 7000 rpm, the spin coating time is 30 s, and the thickness of the PCBM layer is 15 nm. In step (7), the evaporation rate of the thermal evaporation deposition is 0.1 Å / s; the C 60 The layer thickness is 20 nm; In step (8), the evaporation rate of the thermal evaporation deposition is 0.1 Å / s; the thickness of the Ag metal layer is 8 nm; In step (9), the argon flow rate is 30 sccm, the magnetron sputtering power is 45 W, the magnetron sputtering vacuum degree is 0.2 Pa, and the thickness of the ITO transparent top electrode is 200 nm.
[0016] The present invention also provides an application of the aforementioned semi-transparent perovskite solar cell in the cultivation of high-value crops.
[0017] The principle of this invention: This invention addresses the problems of existing semi-transparent perovskite solar cells in high-value crop cultivation applications, such as lack of agricultural orientation in spectral control, limited control methods, and low spectral matching accuracy. It proposes a ternary synergistic spectral control technology to meet the light requirements of high-value crops. This technology achieves selective sieving of the solar spectrum through the synergistic effect of "perovskite bandgap control, absorption layer thickness control, and Ag metal layer optical enhancement," enabling the cell to meet the needs of crop photosynthesis while generating electricity.
[0018] 1. The basic design principle is as follows: High-value crops are highly sensitive to spectral distribution and light intensity changes during their growth process. They require photosynthetically active radiation such as red and blue light, but have lower utilization efficiency in the yellow-green light band. Based on this difference in photosynthetic characteristics, this invention enables the device to maintain a high transmittance level in the 600-700 nm red light band and retain a certain transmittance in the 400-500 nm blue light band, while enhancing the absorption and utilization of the 500-600 nm yellow-green light band. This allows the red and blue light required by the crops to be preferentially transmitted to the planting area, while the yellow-green light band, which has relatively lower utilization efficiency by the crops, is preferentially used for photoelectric conversion, achieving a synergy between spectral transmittance suitable for crop growth and photovoltaic power generation in the non-dominant band.
[0019] 2. The specific working principle of the ternary synergistic regulation mechanism (1) Principle of perovskite absorber layer formulation control (band gap control) The perovskite absorber layer of this invention is FA. a Cs 1-a PbI 3-b Br b Hybrid halogen gradient heterojunction materials, where 0 < a < 1, and b is Br - Replace I - The molar ratio is 0 ≤ b ≤ 3.0. By adjusting the b value, the absorption boundary of the material for different wavelengths of light is changed. The mechanism is as follows: when the band gap increases, the absorption edge shifts to shorter wavelengths (leaning towards blue); when the band gap decreases, absorption is enhanced in the longer wavelength region (leaning towards red). Through this band gap modulation, perovskite preferentially absorbs light in non-photosynthetic dominant wavelengths (such as the yellow-green region), thus determining the absorption boundary for spectral sieving.
[0020] (2) Principle of perovskite absorber layer thickness control (transmittance control) The thickness of the perovskite absorber layer in this invention is controlled within the range of 200-800 nm. By adjusting the thickness, the following functions are achieved: controlling the absorption path length of light in the perovskite absorber layer; adjusting the overall transmittance of the device; and achieving fine-tuning of the transmission / absorption ratio in different wavelength bands. The working mechanism of the perovskite absorber layer is as follows: increasing the thickness enhances absorption and reduces transmittance; decreasing the thickness increases transmittance but reduces power generation capacity. Through thickness optimization, the battery maintains high transmittance in the critical wavelength band of photosynthetically active radiation (PAR) while ensuring effective absorption in non-critical wavelength bands.
[0021] (3) Principle of Ag metal layer modulation (optical enhancement + interface engineering) In C 60 An Ag metal layer with a thickness of 1-10 nm is introduced between the layer and the ITO transparent top electrode. Its structure is either a continuous ultrathin film or a discrete nanoparticle structure, adjacent to C. 60 It is positioned above the layer. The Ag metal layer functions through the following dual mechanism: ① Optical modulation effect: The Ag metal layer, through localized surface plasmon resonance, interface reflection modulation, and local light field redistribution, interacts with PCBM-C 60 The electron transport composite layer and the ITO transparent top electrode work together to change the light propagation path inside the device and the final transmission spectrum distribution, thereby redistributing the transmission ratio of the device to different visible light bands.
[0022] ②Interfacial electrical optimization effect: Ag metal layer improves C 60 Improving the interfacial contact performance between the layer and the ITO electrode can enhance the overall photoelectric conversion performance of the device by reducing interfacial contact resistance, increasing electron extraction efficiency, and suppressing interfacial recombination loss.
[0023] 3. The overall synergistic principle of the ternary synergistic system This invention achieves selective utilization of the solar spectrum by constructing a ternary synergistic system of "perovskite bandgap control - absorption layer thickness control - Ag metal layer optical enhancement". The synergistic division of labor among the three is as follows: perovskite bandgap control is used to determine the material absorption boundary; absorption layer thickness control is used to change the absorption and transmission ratio of different wavelengths of light in the device; and the Ag metal layer further cooperates with the upper functional layer to adjust the optical field distribution and interface electrical properties of the device.
[0024] The optimization goal of the semi-transparent perovskite solar cell of this invention is not simply to pursue the highest photoelectric conversion efficiency (PCE), but to achieve synergistic optimization of key spectral transmittance, AVT, and power generation performance for agricultural applications. It provides an integrated solution of "spectral screening - power generation utilization - environmental control" for high-value crop cultivation, effectively alleviating problems such as strong light burn, high energy consumption for supplemental lighting, and competition for agricultural solar resources.
[0025] The beneficial effects of this invention are: 1. This invention achieves spectral directional modulation to meet the light requirements of high-value crops, enabling semi-transparent perovskite solar cells to maintain a high transmittance in the red light (600~700 nm) band and retain a certain transmittance in the blue light (400~500 nm) band, while preferentially reducing the transmittance in the 500~600 nm yellow-green light band, which is beneficial to improving the photosynthetic efficiency of crops. 2. This invention integrates a ternary control method of perovskite band gap, absorption layer thickness, and Ag intermediate layer optical enhancement, which improves the precision of spectral control, makes the transmission and absorption characteristics of light in different bands clearer, and achieves selective sieving of the spectrum. 3. Semi-transparent perovskite solar cells maintain a low transmittance level relative to the light-transmitting structure of the substrate in the 500~600 nm wavelength band, which is beneficial for prioritizing the adjustment and utilization of light energy with relatively low crop utilization efficiency, thereby improving the overall light energy utilization efficiency. 4. After introducing an Ag metal layer, the semi-transparent perovskite solar cell of the present invention can be coupled with PCBM-C 60 The synergistic effect of the electron transport composite layer and the ITO transparent top electrode modulates the internal optical field distribution and transmission spectrum of the device, while improving the interfacial electrical properties, enhancing electron extraction efficiency and reducing recombination loss, thereby improving the overall performance of the device. 5. This invention achieves synergistic optimization of spectral modulation and photovoltaic power generation performance, improving the overall energy utilization efficiency of the system while ensuring crop growth requirements; 6. This invention provides an integrated solution of "spectral screening - power generation utilization - environmental control" for high-value crop cultivation, effectively alleviating problems such as strong light scorching, high energy consumption of supplemental lighting, and competition for agricultural solar resources, and realizing the dual benefits of photovoltaic power generation and crop growth in facility agriculture. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the structure of a semi-transparent perovskite solar cell; In the figure, 1 is the ITO conductive glass bottom electrode, and 2 is the NiO electrode. x Interface decoration layer, 3 is 4PADCB hole transport layer, 4 is FA a Cs 1-a PbI 3-b Br b Perovskite absorber layer, 5 is PCBM-C 60 Electron transport composite layer, 6 is Ag metal layer, 7 is ITO transparent top electrode; Figure 2 A comparison of the JV characteristic curves of semi-transparent perovskite solar cell 1 and semi-transparent perovskite solar cell D1; Figure 3A comparison of the transmittance spectra of semi-transparent perovskite solar cell 1 and semi-transparent perovskite solar cell D1; Figure 4 Absorption spectra of semi-transparent perovskite solar cells 1, 5, and 8; Figure 5 Tauc fitting plots for semi-transparent perovskite solar cells 1, 5, and 8; Figure 6 The transmittance spectra of semi-transparent perovskite solar cells 4, 5, and 6 are shown. Figure 7 The transmittance spectra of semi-transparent perovskite solar cells 7, 8, and 9 are shown. Figure 8 Transmittance spectra of semi-transparent perovskite solar cells 1, 2, and 3; Figure 9 JV curves for semi-transparent perovskite solar cells 1, 2, and 3; Figure 10 The filtered solar spectra of semi-transparent perovskite solar cells 1, 2, and 3 are shown. Figure 11 The graph shows the integrated transmittance of semi-transparent perovskite solar cells 1, D2, and D3 in the 400–500 nm, 500–600 nm, and 600–700 nm wavelength bands. Detailed Implementation
[0027] The present invention will now be described in further detail with reference to specific embodiments, so that those skilled in the art can understand it.
[0028] Example 1 Fabrication of a semi-transparent perovskite solar cell 1 Combination Figure 1 As shown, the semi-transparent perovskite solar cell 1 in this embodiment includes an ITO conductive glass bottom electrode and a NiO electrode arranged sequentially from bottom to top. x Interface decoration layer, 4PADCB hole transport layer, FA 0.95 Cs 0.05 PbBr3 perovskite absorber layer, PCBM-C 60 Electron transport composite layer, Ag metal layer and ITO transparent top electrode.
[0029] The preparation process is as follows: 1. ITO conductive glass bottom electrode treatment: (1) ITO conductive glass (sheet resistance 15Ω / sq) was used as the bottom electrode and ultrasonically cleaned in sequence with glass water, deionized water and anhydrous ethanol. Each ultrasonic cleaning time was 20 min. (2) After cleaning, nitrogen gas is blown dry, and then ultraviolet ozone treatment is performed for 25 min to remove organic impurities on the surface and improve the surface hydrophilicity to obtain ITO conductive glass bottom electrode.
[0030] 2. NiO x Interface finishing layer spin coating: (1) Dissolve NiO nanoparticles in deionized water to prepare a NiO solution with a concentration of 10 mg / mL; (2) NiO solution was spin-coated as an interface modification layer on the surface of the ITO conductive glass bottom electrode using a spin-coating method. The spin-coating speed was 4000 rpm and the spin-coating time was 30s. (3) After spin coating, anneal at 120℃ for 10 min, with the thickness controlled at 10 nm, to obtain NiO. x Interface decoration layer.
[0031] 3. Spin coating of 4PADCB hole transport layer: (1) Dissolve 4PADCB powder (Shanghai Weizhu) in anhydrous ethanol to prepare a 4PADCB solution with a concentration of 0.5 mg / mL; (2) In NiO x The interface modification layer surface was coated with 4PADCB solution as a hole transport layer by spin coating at a speed of 3000 rpm and a spin coating time of 30 s. (3) After spin coating, anneal at 100℃ for 10 min, and control the thickness to 10 nm to obtain 4PADCB hole transport layer.
[0032] 4. FA 0.95 Cs 0.05 Preparation of PbBr3 perovskite absorber layer: (1) Configure FA 0.95 Cs 0.05 PbBr3 precursor solution: CsBr (Biolight), FABr (Biolight), and PbBr2 (TCL) were dissolved in a DMF-DMSO mixed solvent (DMF and DMSO volume ratio 4:1) at a molar ratio of 0.05:0.95:1 to obtain FABr3 with a total molar concentration of 0.7 mol / L. 0.95 Cs 0.05 PbBr3 precursor solution; (2) Add 40 μL of FA 0.95 Cs 0.05 PbBr3 precursor solution was spin-coated onto the surface of 4PADCB hole transport layer at 4000 rpm for 23 s. During the spin-coating process, 150 μL of chlorobenzene antisolvent was added dropwise at the 12th s. (3) After spin coating, anneal at 100℃ for 20 min to form FA with a thickness of 300 nm.0.95 Cs 0.05 PbBr3 perovskite absorber layer.
[0033] 5. PCBM-C 60 Fabrication of electron transport composite layer: (1) PCBM ([6,6]-phenyl-C 61 methyl butyrate (Biolight) was dissolved in chlorobenzene to obtain a PCBM solution with a concentration of 10 mg / mL; (2) In FA 0.95 Cs 0.05 PCBM solution was spin-coated onto the surface of the PbBr3 perovskite absorber layer at a spin speed of 7000 rpm for 30 s to form a PCBM layer with a thickness of 15 nm. (3) Subsequently, C was thermally evaporated and deposited on the surface of the PCBM layer. 60 Layer (fullerene C) 60 (Boraite), evaporation rate 0.1 Å / s, C 60 The thickness of the layer is controlled at 20 nm, and the PCBM layer and C 60 The layer combination is PCBM-C 60 Electron transport composite layer.
[0034] 6. Ag metal layer thermal evaporation: A thermal evaporation deposition device is used on PCBM-C 60 An Ag layer is deposited on the surface of the electron transport composite layer as a metal intermediate layer. The evaporation rate is 0.1 Å / s and the deposition thickness is precisely controlled to 8 nm, forming an Ag metal layer with a continuous nanoparticle structure, thereby achieving a localized surface plasmon resonance effect.
[0035] 7. Deposition of ITO transparent top electrode: Under an argon atmosphere, an ITO layer was deposited on the surface of the Ag metal layer as a transparent top electrode using magnetron sputtering. The magnetron sputtering power was 45W, the argon flow rate was 30 sccm, the vacuum degree of magnetron sputtering was 0.2Pa, and the deposition thickness was precisely controlled to 200nm to obtain the ITO transparent top electrode, thus completing the fabrication of the semi-transparent perovskite solar cell 1.
[0036] Examples 2 to 9 were used to verify the effect of the thickness of the perovskite absorber layer on the transmission characteristics, absorption behavior and photovoltaic performance of the device. Absorber layers of different thicknesses were prepared by adjusting the precursor concentration, and the rationality of the thickness range and preferred thickness design defined in this invention was further explained.
[0037] Example 2 Fabrication of a semi-transparent perovskite solar cell 2 The semi-transparent perovskite solar cell 2 in this embodiment is the same as that in Example 1, except that in step 4, FA... 0.95 Cs 0.05The total molar concentration of the PbBr3 precursor solution was 0.5 mol / L, and the prepared FA 0.95 Cs 0.05 The thickness of the PbBr3 perovskite absorber layer is 200 nm.
[0038] Example 3 Fabrication of a semi-transparent perovskite solar cell 3 The semi-transparent perovskite solar cell 3 in this embodiment is the same as that in Example 1, except that in step 4, FA 0.95 Cs 0.05 The total molar concentration of the PbBr3 precursor solution was 1 mol / L, and the prepared FA 0.95 Cs 0.05 The thickness of the PbBr3 perovskite absorber layer is 450 nm.
[0039] Example 4 Fabrication of a semi-transparent perovskite solar cell 4 The semi-transparent perovskite solar cell 4 in this embodiment is the same as that in Example 1, except that in step 4, the perovskite absorber layer is FA. 0.95 Cs 0.05 PbI3 perovskite absorber layer, FA 0.95 Cs 0.05 The preparation method of the PbI3 perovskite absorber layer is as follows: (1) Preparation of FA 0.95 Cs 0.05 PbI3 precursor solution: CsI (Biolight), FAI (Biolight), and PbI2 (TCL) were dissolved in a DMF-DMSO mixed solvent at a molar ratio of 0.05:0.95:1 (DMF and DMSO volume ratio of 4:1) to obtain a total molar concentration of 0.5 mol / L for FAI. 0.95 Cs 0.05 PbI3 precursor solution; (2) Add 40 μL of FA 0.95 Cs 0.05 PbI3 precursor solution was spin-coated onto the surface of 4PADCB hole transport layer at 2000 rpm for 10 s and then at 4000 rpm for 40 s. During the total spin-coating process (total spin-coating time of 50 s), 150 μL of chlorobenzene antisolvent was added at 42 s. (3) After spin coating, anneal at 100℃ for 20 min to form FA with a thickness of 300 nm. 0.95 Cs 0.05 PbI3 perovskite absorber layer.
[0040] Example 5 Fabrication of a semi-transparent perovskite solar cell 5 The semi-transparent perovskite solar cell 5 in this embodiment is the same as that in Example 4, except that in step 4, FA 0.95 Cs 0.05 The total molar concentration of the PbI3 precursor solution was 0.75 mol / L, and the prepared FA 0.95 Cs 0.05 The thickness of the PbI3 perovskite absorber layer is 500 nm.
[0041] Example 6 Fabrication of a semi-transparent perovskite solar cell 6 The semi-transparent perovskite solar cell 6 in this embodiment is the same as that in Example 4, except that in step 4, FA 0.95 Cs 0.05 The total molar concentration of the PbI3 precursor solution was 1.5 mol / L, and the prepared FA 0.95 Cs 0.05 The thickness of the PbI3 perovskite absorber layer is 800 nm.
[0042] Example 7 Fabrication of a semi-transparent perovskite solar cell 7 The semi-transparent perovskite solar cell 7 in this embodiment is the same as that in Example 1, except that in step 4, the perovskite absorber layer is FA. 0.95 Cs 0.05 PbI 2.2 Br 0.8 Perovskite absorber layer, FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 The preparation method of the perovskite absorber layer is as follows: (1) Preparation of FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 Precursor solution: CsI (Biolight), FAI (Biolight), PbBr2 (TCL), and PbI2 (TCL) were dissolved in a molar ratio of 0.05:0.95:0.4:0.6 in a DMF-DMSO mixed solvent (DMF and DMSO volume ratio of 4:1) to obtain a total molar concentration of 0.5 mol / L for FAI. 0.95 Cs 0.05 PbI 2.2 Br 0.8 Precursor solution; (2) Add 40 μL of FA 0.95 Cs 0.05 PbI 2.2 Br 0.8The precursor solution was spin-coated onto the surface of the 4PADCB hole transport layer at 4000 rpm for 23 s. During the spin-coating process, 150 μL of chlorobenzene antisolvent was added dropwise at the 12th s. (3) After spin coating, anneal at 100℃ for 20 min to form FA with a thickness of 240 nm. 0.95 Cs 0.05 PbI 2.2 Br 0.8 Perovskite absorber layer.
[0043] Example 8 Fabrication of a semi-transparent perovskite solar cell 8 The semi-transparent perovskite solar cell 8 in this embodiment is the same as that in Example 7, except that in step 4, FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 The total molar concentration of the precursor solution was 0.75 mol / L, and the prepared FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 The thickness of the perovskite absorber layer is 360 nm.
[0044] Example 9 Fabrication of a semi-transparent perovskite solar cell 9 The semi-transparent perovskite solar cell 9 in this embodiment is the same as that in Example 7, except that in step 4, FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 The total molar concentration of the precursor solution was 1.25 mol / L, and the prepared FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 The thickness of the perovskite absorber layer is 600 nm.
[0045] The relationship between the precursor solution concentration and the corresponding perovskite absorber layer thickness in Examples 1-9 is shown in Table 1.
[0046] Table 1 Relationship between precursor concentration and corresponding perovskite absorber layer thickness Comparative Example 1 Fabrication of a semi-transparent perovskite solar cell D1 The semi-transparent perovskite solar cell D1 in this comparative example is the same as that in Example 1, except that: the semi-transparent perovskite solar cell D1 in this comparative example includes an ITO conductive glass bottom electrode and a NiO electrode arranged sequentially from bottom to top. xInterface decoration layer, 4PADCB hole transport layer, FA 0.95 Cs 0.05 PbBr3 perovskite absorber layer, PCBM-C 60 The electron transport composite layer and the ITO transparent top electrode are missing an Ag metal layer. This comparative example is used to verify the role of the Ag metal layer in the battery structure of this invention.
[0047] Comparative Example 2 Fabrication of the semi-transparent perovskite solar cell D2 The semi-transparent perovskite solar cell D2 in this comparative example is the same as that in Example 1, except that: the semi-transparent perovskite solar cell D2 in this comparative example includes an ITO conductive glass bottom electrode and a NiO electrode arranged sequentially from bottom to top. x Interface decoration layer and 4PADCB hole transport layer; Comparative Example 3 Fabrication of the semi-transparent perovskite solar cell D3 The semi-transparent perovskite solar cell D3 in this comparative example is the same as that in Example 1, except that: the semi-transparent perovskite solar cell D3 in this comparative example includes an ITO conductive glass bottom electrode and a NiO electrode arranged sequentially from bottom to top. x Interface decoration layer, 4PADCB hole transport layer and FA 0.95 Cs 0.05 PbBr3 perovskite absorber layer.
[0048] Performance testing I. Optical Enhancement Performance Testing of Ag Metal Layers Photovoltaic performance and transmittance spectroscopy tests were performed on the semi-transparent perovskite solar cell 1 of Example 1 and the semi-transparent perovskite solar cell D1 of Comparative Example 1, respectively.
[0049] The results are shown in Table 2. Figure 2 and Figure 3 As shown: The open-circuit voltage Voc of the semi-transparent perovskite solar cell 1 is 1.53 V, and the short-circuit current density Jsc is 7.41 mA / cm². 2 The fill factor (FF) is 81.2%, the power conversion efficiency (PCE) is 9.21%, and the average visible light transmittance (AVT) is 72.1%. The semi-transparent perovskite solar cell D1 has a Voc of 1.49 V and a Jsc of 7.32 mA / cm². 2 The FF was 77.5%, PCE was 8.25%, and AVT was 57.6%. Compared with Example 1, without the introduction of the Ag metal layer, the short-circuit current density, fill factor, and photoelectric conversion efficiency of the device all decreased, while the average visible light transmittance also decreased from 72.1% to 57.6%.
[0050] The above results demonstrate that the introduction of an Ag metal layer contributes to improved overall device performance. On one hand, the Ag metal layer improves the interfacial contact between the C60 layer and the transparent top electrode, increasing carrier extraction efficiency and reducing interfacial recombination losses, thereby resulting in higher Jsc, FF, and PCE. On the other hand, combined with the multilayer structure design of the device of this invention, the Ag metal layer and the PCBM-C... 60 The electron transport composite layer and the ITO transparent top electrode work together to maintain a better transmission-power generation balance. Based on the current results, it can be confirmed that the Ag metal layer has a positive effect on improving the overall performance of the device; as for the specific changes in the transmission spectrum at different wavelengths, these are the result of the synergistic effect of Ag and the multilayer optical structure.
[0051] Table 2. Photovoltaic performance statistics of semi-transparent perovskite solar cells 1 and D1. Note: Test light intensity: AM1.5G, 100 mW / cm² 2 AVT is the average visible light transmittance of 400~700 nm.
[0052] II. FA a Cs 1-a PbI 3-b Br b Performance testing of perovskite absorber layer 1. The absorption spectra of semi-transparent perovskite solar cells 1, 5, and 8 were detected respectively, and Tauc fitting was performed on the absorption spectra.
[0053] The results are as follows Figure 4 and Figure 5 As shown, with the increase of Br in the perovskite absorber layer - As the content decreases, the absorption edge of the material gradually shifts towards longer wavelengths, exhibiting significant bandgap modulation characteristics. FA 0.95 Cs 0.05 PbBr3, FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 and FA 0.95 Cs 0.05 The absorption edge of PbI3 shifts sequentially towards the red light region, with corresponding optical band gaps of 2.28 eV, 1.77 eV, and 1.53 eV, respectively. These results indicate that by adjusting the FA... a Cs 1-a PbI 3-b Br b Br in perovskite - with I -The composition ratio can effectively control the band gap and spectral absorption range of the material, thus providing a basis for the selective utilization of different wavelength bands in the device.
[0054] 2. The transmittance spectra of the semi-transparent perovskite solar cells 1-9 in Examples 1-9 were detected respectively.
[0055] The results are as follows Figure 6 As shown, for FA 0.95 Cs 0.05 In the PbI3 system, as the precursor concentration increased from 0.5 mol / L to 1.5 mol / L, the thickness of the perovskite absorber layer gradually increased, and the overall transmittance of the device gradually decreased. The transmittance decrease was particularly significant in the 500–700 nm wavelength range, indicating that a thicker absorber layer can enhance the absorption and utilization of visible light. These results demonstrate that the transmittance of the device can be continuously controlled by adjusting the thickness of the perovskite absorber layer.
[0056] The results are as follows Figure 7 As shown, for FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 In this system, the transmittance of the device also decreases with increasing absorber layer thickness. Specifically, the transmittance decreases across all wavelengths in the visible light region, indicating that a thicker perovskite absorber layer enhances the absorption and utilization of incident light. Figure 6 FA shown 0.95 Cs 0.05 Compared to the PbI3 system, FA 0.95 Cs 0.05 PbI 2.2 Br 0.8 The system exhibits different transmittance distribution characteristics in the visible light region, indicating that variations in the perovskite composition affect the spectral transmission behavior of the device. These results demonstrate that the transmittance of the device can be effectively adjusted by controlling the thickness and composition of the perovskite absorption layer.
[0057] The results are as follows Figure 8 As shown, for FA 0.95 Cs 0.05 In the PbBr3 system, as the precursor concentration increased from 0.5 mol / L to 1.0 mol / L and the perovskite absorber layer thickness increased from 200 nm to 450 nm, the transmittance of the device gradually decreased in the 400–700 nm range. The transmittance decreased most significantly in the 500–600 nm band, while maintaining a relatively high transmittance level in the 600–700 nm band. These results indicate that by adjusting the FA… 0.95 Cs 0.05The thickness of the PbBr3 absorber layer can effectively adjust the transmittance ratio of different visible light bands, providing a foundation for the subsequent construction of semi-transparent perovskite solar cells that take into account both agricultural lighting needs and photovoltaic power generation performance.
[0058] 3. Based on the aforementioned component screening results, FA with superior overall performance was selected. 0.95 Cs 0.05 Using the PbBr3 system as the research object, we further investigated the influence of the thickness of the perovskite absorber layer on the light transmittance and photovoltaic performance of the device.
[0059] The visible spectra of the semi-transparent perovskite solar cells 1-3 in Examples 1-3 were detected, and the JV curves of the semi-transparent perovskite solar cells 1-3 were tested. Finally, the integrated transmittance of the three bands of 400-500 nm, 500-600 nm, and 600-700 nm were statistically analyzed to compare the transmittance selectivity of the target band under different thickness conditions.
[0060] Table 3. Statistical table of cell thickness, AVT, transmittance by wavelength and photovoltaic performance for different absorber layers. Note: Test light intensity: AM 1.5G, 100 mW / cm² 2 AVT is the average visible light transmittance of 400~700 nm.
[0061] The results are shown in Table 3. Figure 8 and Figure 9 As shown, with FA 0.95 Cs 0.05 As the concentration of the PbBr3 precursor solution increases and the thickness of the absorption layer increases, the absorption of visible light by the battery gradually increases, and its light transmittance and photovoltaic performance show a clear trade-off.
[0062] Specifically, regarding light transmittance, the integrated transmittance of the semi-transparent perovskite solar cells 2, 1, and 3 in the 400–500 nm wavelength range are 50.6%, 31.1%, and 21.0%, respectively; in the 500–600 nm wavelength range, they are 71.8%, 62.7%, and 58.1%; and in the 600–700 nm wavelength range, they are 86.2%, 93.2%, and 85.3%, respectively, with corresponding AVTs of 74.6%, 72.1%, and 64.4%. It is evident that as the thickness of the perovskite absorption layer increases, the integrated transmittance of the cells in the 400–500 nm and 500–600 nm wavelength ranges generally decreases, indicating that a thicker perovskite absorption layer enhances the absorption and utilization of blue and yellow-green light wavelengths. For the 600-700 nm band, all samples maintained a high transmittance level. Among them, the 300 nm thick sample showed a higher integrated transmittance (93.2%), indicating that the transmittance characteristics in this band are affected not only by the thickness of the absorption layer, but also by the optical modulation effect of the multilayer structure of the device.
[0063] In terms of photovoltaic performance, the overall performance of the cell improves with increasing thickness of the perovskite absorber layer. The Voc values of semi-transparent perovskite solar cells 2, 1, and 3 are 1.5 V, 1.53 V, and 1.61 V, respectively, and their Jsc values are 6.92 mA / cm². 2 7.41 mA / cm 2 and 7.55 mA / cm 2 The light absorption fractions (FF) were 75.8%, 81.2%, and 85.1%, respectively, and the power conversion efficiency (PCE) was 7.87%, 9.21%, and 10.48%, respectively. These results indicate that thickening the perovskite absorber layer enhances light absorption and improves the cell's output performance, thereby increasing the overall photoelectric conversion efficiency.
[0064] It should be noted that the preferred criteria of this invention are not solely focused on achieving the highest photoelectric conversion efficiency (PCE), but rather on the comprehensive balance between key spectral retention, average visible light transmittance (AVT), and power generation performance in agricultural applications. Analysis of both transmittance and power generation performance reveals that while the semi-transparent perovskite solar cell 2 exhibits the highest transmittance and AVT, its relatively thin perovskite absorber layer results in relatively low Voc, Jsc, FF, and PCE. While the semi-transparent perovskite solar cell 3 achieves the highest photovoltaic conversion efficiency, its AVT and transmittance in the three target visible light bands decrease significantly, making it unsuitable for applications requiring high light transmittance and specific spectral transmittance. In contrast, the semi-transparent perovskite solar cell 1 maintains high transmittance while exhibiting superior photovoltaic output performance, particularly maintaining a high transmittance of 93.2% in the 600–700 nm band, while achieving a PCE of 9.21%, demonstrating a better overall balance between transmittance and power generation. Therefore, the semi-transparent perovskite solar cell 1 possesses the best overall balance performance between transmittance and power generation.
[0065] The results of performance test 2 show that the thickness of the perovskite absorber layer is a crucial factor affecting the synergistic optimization of the spectral transmittance characteristics and photovoltaic performance of semi-transparent perovskite solar cells. By rationally controlling the thickness of the perovskite absorber layer, it is possible to ensure the transmission of blue and red light while also considering the absorption and utilization of other visible light bands and the overall power generation performance of semi-transparent perovskite solar cells.
[0066] In summary, this invention utilizes FA... 0.95 Cs 0.05 Using PbBr3 as the perovskite absorber layer material, combined with a 300 nm thick perovskite absorber layer and an 8 nm Ag metal layer, the semi-transparent perovskite solar cell 1 achieves good spectral tuning capability and photoelectric output performance. Test results show that this semi-transparent perovskite solar cell 1, while maintaining a certain degree of translucency, can directionally redistribute the transmitted solar spectrum. While maintaining a high transmittance level in the 600–700 nm band, it maintains a relatively low transmittance ratio in the 500–600 nm band. This facilitates the transmission of red light and some blue light, which are more needed by high-value crops, to the planting area, while preferentially utilizing some non-dominant wavelengths for photoelectric conversion.
[0067] Example 10 Application of semi-transparent perovskite solar cells 1 This embodiment verifies the feasibility of applying the semi-transparent perovskite solar cell 1 of the present invention in high-value crop planting scenarios, focusing on the cell's filtering behavior of the solar spectrum and its ability to retain key photosynthetic wavelengths of crops. According to the design objectives of the present invention, the cell should preferentially transmit 400-500 nm blue light and 600-700 nm red light, while enhancing the absorption and utilization of 500-600 nm yellow-green light, to achieve a synergy between spectral transmittance suitable for crop growth and photovoltaic power generation in non-dominant wavelength bands. Semi-transparent perovskite solar cells D2 and D3 were selected as comparative samples. Semi-transparent perovskite solar cell D2 is a substrate control sample without the introduction of a perovskite absorber layer and top electrode structure; semi-transparent perovskite solar cell D3 is an intermediate structure sample with the introduction of a perovskite absorber layer; and semi-transparent perovskite solar cell 1 is a complete device sample.
[0068] The transmittance spectrum of the semi-transparent perovskite solar cell 1 in Example 1 was measured in the 400–900 nm wavelength range using a UV-Vis spectrophotometer. Combined with the standard solar spectral distribution, the filtered solar spectrum after transmission was calculated. Furthermore, the transmittance spectrum was divided into three characteristic bands: 400–500 nm, 500–600 nm, and 600–700 nm, and the average or integrated transmittance of each band was calculated.
[0069] The results are as follows Figure 10 and Figure 11 As shown, compared with the semi-transparent perovskite solar cell D2, the semi-transparent perovskite solar cell D3 with the addition of the perovskite absorber layer has significantly reduced transmittance in the 400~500 nm and 500~600 nm wavelength bands, while maintaining a high transmittance level in the 600~700 nm wavelength band. This indicates that the perovskite absorber layer can significantly modulate the incident solar spectrum and preferentially reduce some short-wave and yellow-green light bands.
[0070] After further introducing a PCBM-C60 electron transport composite layer, an Ag metal layer, and an ITO transparent top electrode to form a complete device, the transmittance of the semi-transparent perovskite solar cell 1 in the 400–500 nm blue light band is 31.1%, close to that of D3 (28.2%); the transmittance in the 500–600 nm yellow-green light band is 62.7%, basically equivalent to that of D3 (61.4%), and significantly lower than that of D2 (87.5%); the transmittance in the 600–700 nm red light band increases from 82.2% of D3 to 93.2%. These results indicate that the semi-transparent perovskite solar cell 1 does not simply improve the overall transmittance, but rather significantly improves the transmittance in the 600–700 nm red light band while maintaining the reduction effect in the 500–600 nm yellow-green light band, thereby achieving directional reconstruction of the transmitted solar spectrum.
[0071] As shown in Table 4, the semi-transparent perovskite solar cell D2, as a substrate control, exhibits high transmittance in all three characteristic wavelength bands. After the introduction of the perovskite absorber layer, the transmittance of the semi-transparent perovskite solar cell D3 in the 400-500 nm and 500-600 nm wavelength bands decreased significantly, with the most significant reduction in yellow-green light in the 500-600 nm band, indicating that the perovskite absorber layer is the main functional layer for spectral sieving. Compared to the semi-transparent perovskite solar cell D3, the semi-transparent perovskite solar cell 1 showed a significant increase in transmittance in the 600-700 nm red light band, while maintaining similar levels in the 400-500 nm blue light band and the 500-600 nm yellow-green light band, indicating that the complete device can further enhance red light transmittance while maintaining the reduction effect in the yellow-green light band. In summary, the semi-transparent perovskite solar cell 1 of this invention can achieve a redistribution of the transmitted spectrum through the synergistic effect of the multi-layer structure. This allows the spectrum transmitted to the crop canopy to retain the key red light band and maintain a certain supply of blue light while reducing the proportion of some non-dominant bands, demonstrating its application potential for high-value crop planting scenarios.
[0072] Table 4. Transmittance and AVT statistics of application verification samples in different wavelength bands. Note: AVT is the average visible light transmittance of 400~700 nm.
[0073] In summary, the semi-transparent perovskite solar cell of this invention can not only output electrical energy as a power generation device, but also functionally modulate the spectrum of incident sunlight as a covering material for facility agriculture. This semi-transparent perovskite solar cell has application value in combining spectral modulation with photovoltaic power generation, and can provide technical support for optimizing the light environment and energy utilization in high-value crop cultivation environments.
[0074] All other parts not described in detail are existing technologies. Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A semi-transparent perovskite solar cell, characterized in that: The semi-transparent perovskite solar cell includes an ITO conductive glass bottom electrode and a NiO electrode arranged sequentially from bottom to top. x Interface decoration layer, 4PADCB hole transport layer, FA 0.95 Cs 0.05 PbBr3 perovskite absorber layer, PCBM-C 60 Electron transport composite layer, Ag metal layer and ITO transparent top electrode; The PCBM-C 60 The electron transport composite layer includes a PCBM layer and a C layer disposed on the surface of the PCBM layer. 60 layer; The Ag metal layer is disposed on the C 60 Between the layer and the ITO transparent top electrode; The NiO x The thickness of the interface modification layer is 10~20 nm; the thickness of the 4PADCB hole transport layer is 10~15 nm; the FA 0.95 Cs 0.05 The thickness of the PbBr3 perovskite absorber layer is 200~450 nm; the thickness of the PCBM layer is 15~20 nm; the C 60 The thickness of the layer is 20~25 nm; the thickness of the Ag metal layer is 1~10 nm; and the thickness of the ITO transparent top electrode is 200~250 nm.
2. The semi-transparent perovskite solar cell according to claim 1, characterized in that: The NiO x The thickness of the interface modification layer is 10 nm; the thickness of the 4PADCB hole transport layer is 10 nm. The FA 0.95 Cs 0.05 The thickness of the PbBr3 perovskite absorber layer is 300 nm; The thickness of the PCBM layer is 15 nm; the C 60 The thickness of the layer is 20 nm; the thickness of the Ag metal layer is 8 nm; and the thickness of the ITO transparent top electrode is 200 nm.
3. A method for preparing a semi-transparent perovskite solar cell according to any one of claims 1 to 2, characterized in that: Includes the following steps: (1) The ITO conductive glass was ultrasonically cleaned, dried with nitrogen, and then treated with ultraviolet ozone to obtain the ITO conductive glass bottom electrode. (2) NiO solution was spin-coated onto the surface of an ITO conductive glass bottom electrode using a spin-coating method. After spin-coating, annealing was performed to obtain NiO. x Interface decoration layer; (3) The 4PADCB solution was spin-coated onto NiO. x The interface modification layer surface is spin-coated, and then annealed to obtain a 4PADCB hole transport layer. (4) Cesium bromide, formamidine hydrobromide and lead bromide are dissolved in a DMF-DMSO mixed solvent to obtain a precursor solution; (5) The precursor solution was spin-coated onto the surface of the 4PADCB hole transport layer using a spin-coating method. Chlorobenzene antisolvent was added dropwise during spin-coating. After spin-coating, annealing was performed to obtain FA. 0.95 Cs 0.05 PbBr3 perovskite absorber layer; (6) The PCBM solution was spin-coated onto the FA. 0.95 Cs 0.05 Spin-coating was performed on the surface of the PbBr3 perovskite absorber layer to obtain the PCBM layer; (7) C is deposited on the surface of the PCBM layer using thermal evaporation deposition method. 60 Layer, PCBM layer and C 60 The layer combination is PCBM-C 60 Electron transport composite layer; (8) Using thermal evaporation deposition method on PCBM-C 60 An Ag layer is deposited on the surface of the electron transport composite layer to obtain an Ag metal layer; (9) An ITO layer was deposited on the surface of the Ag metal layer by magnetron sputtering to obtain an ITO transparent top electrode, thus completing the fabrication of a semi-transparent perovskite solar cell.
4. The preparation method according to claim 3, characterized in that: In step (1), ultrasonic cleaning is performed sequentially using glass water, deionized water and anhydrous ethanol, and the ultraviolet ozone treatment time is 20~30 min. In steps (2) and (3), the concentration of the NiO solution is 10-15 mg / mL, the concentration of the 4PADCB solution is 0.5-1 mg / mL, the spin coating speed is 3000-4000 rpm, the spin coating time is 30-40 s, the annealing temperature is 100-120℃, and the annealing time is 10-15 min; the NiO x The thickness of the interface modification layer is 10~20 nm; the thickness of the 4PADCB hole transport layer is 10~15 nm. In step (4), the molar ratio of cesium bromide, formamidine hydrobromide and lead bromide is 0.05:0.95:1, the volume ratio of DMF to DMSO in the DMF-DMSO mixed solvent is 3~4:1, and the total molar concentration of the precursor solution is 0.5~1.5mol / L. In step (5), the spin coating speed is 2000~4000 rpm, the spin coating time is 23~50 s, and chlorobenzene antisolvent is added dropwise during the 12th~42nd s of the spin coating process. The volume ratio of chlorobenzene antisolvent to precursor solution is 1:0.2~0.
4. The annealing temperature is 100~120℃, and the annealing time is 20~25 min. 0.95 Cs 0.05 The thickness of the PbBr3 perovskite absorber layer is 200~450 nm.
5. The preparation method according to claim 4, characterized in that: In step (1), ultrasonic cleaning is performed sequentially using glass water, deionized water and anhydrous ethanol, and the ultraviolet ozone treatment time is 25 min. In steps (2) and (3), the concentration of the NiO solution is 10 mg / mL, and the concentration of the 4PADCB solution is 0.5 mg / mL; the NiO x The thickness of the interface modification layer is 10 nm; the thickness of the 4PADCB hole transport layer is 10 nm. In step (4), the volume ratio of DMF to DMSO in the DMF-DMSO mixed solvent is 4:1, and the total molar concentration of the precursor solution is 0.7 mol / L. In step (5), the spin coating speed is 4000 rpm, the spin coating time is 23 s, and chlorobenzene antisolvent is added dropwise at the 12th second of the spin coating process. The volume ratio of chlorobenzene antisolvent to precursor solution is 1:0.
27. The annealing temperature is 100℃, and the annealing time is 20 min. 0.95 Cs 0.05 The thickness of the PbBr3 perovskite absorber layer is 300 nm.
6. The preparation method according to claim 3, characterized in that: In step (6), the concentration of the PCBM solution is 10~15 mg / mL, the spin coating speed is 7000~8000 rpm, the spin coating time is 30~35 s, and the thickness of the PCBM layer is 15~20 nm. In step (7), the evaporation rate of the thermal evaporation deposition is 0.1~0.2 Å / s; the C 60 The thickness of the layer is 20~25 nm; In step (8), the evaporation rate of the thermal evaporation deposition is 0.1~0.2 Å / s; the thickness of the Ag metal layer is 1~10 nm; In step (9), the atmosphere of the magnetron sputtering method is argon, the flow rate of argon is 30~40 sccm, the power of magnetron sputtering is 45~50 W, the vacuum degree of magnetron sputtering is 0.2~0.4 Pa, and the thickness of the ITO transparent top electrode is 200~250 nm.
7. The preparation method according to claim 6, characterized in that: In step (6), the concentration of the PCBM solution is 10 mg / mL, the spin coating speed is 7000 rpm, the spin coating time is 30 s, and the thickness of the PCBM layer is 15 nm. In step (7), the evaporation rate of the thermal evaporation deposition is 0.1 Å / s; the C 60 The layer thickness is 20 nm; In step (8), the evaporation rate of the thermal evaporation deposition is 0.1 Å / s; the thickness of the Ag metal layer is 8 nm; In step (9), the argon flow rate is 30 sccm, the magnetron sputtering power is 45 W, the magnetron sputtering vacuum degree is 0.2 Pa, and the thickness of the ITO transparent top electrode is 200 nm.
8. The application of a semi-transparent perovskite solar cell according to any one of claims 1 to 2 in the cultivation of high-value crops.
Citation Information
Patent Citations
Semitransparent CsPbI2Br perovskite solar cell based on microcavity spectrum selective electrode, preparation method and application of semitransparent CsPbI2Br perovskite solar cell
CN118139433A
Perovskite solar cell and preparation method and application thereof
CN120711926A
Novel sunglasses based on perovskite photovoltaic material
CN121276815A
